Art for Healthcare: A Review of Artists and Their Ideations - Nurhaya Baniyamin; Ain Farhana Binti Mohd Nazri (Cultural Syndrome, 2020)
Recently there is an increase in interest to use art as a part of the healthcare healing process and environment. The artwork is now regularly set as a condition in design feature for hospitals. The benefits of art in hospitals and medical institutions have been confirmed by numerous studies and subjective evidence. The artwork produced can be a commission collection or a seamless development of interior design concepts. This paper attempts to compile and discuss a range of artistic works and artists that specialize in nature and abstractions of nature which have contributed to healthcare or the healing environment. The paper highlights their thoughts and ideas on the making of their concepts and the way certain techniques help achieve their artistic works. The guidelines published in a study will also be reviewed. Selecting the right artwork for a medical facility requires various thoughts and concern. This includes choosing landscapes and nature-based art, avoiding abstract art, and choosing the right colours for art. Notably, there are many benefits for patients in using beautiful wall art for hospitals and healthcare facilities. The paper reckoned that the primary goal for the patient's well-being is choosing art that can help the patient and improve the overall aesthetic quality of the space. The integration of the healing environment into medicine has taken a more holistic approach and has turned the hospital environment into a place of courage that impacts both staff and patients' well-being. Visual stimulation of nature, natural lighting, artwork, relaxing colours and therapeutic sound can greatly accelerate the therapeutic process. The paper concluded that when art is considered an integral part of hospital design, this will maximize the benefits of arts in healthcare facilities.